Efficacy and safety of etanercept in psoriasis and psoriatic arthritis in the PRESTA study: analysis in patients from Central and Eastern Europe. (2nd January 2018) - Damjanov, Nemanja; Karpati, Sarolta; Kemeny, Lajos; Bakos, Noemi; Bobic, Branislav; Majdan, Maria; Tlustochowicz, Witold; Vitek, Petr; Dokoupilova, Eva; Aldinc, Emre; Szumski, Annette
Abstract: Background: Data are limited on the effectiveness of anti-TNF and other biologics on psoriatric arthritis (PsA) in Central and Eastern Europe (CEE). The objective of this analysis was to evaluate the efficacy of etanercept (ETN) in PsA patients from CEE. Methods: In PRESTA, patients were randomized to receive ETN 50 mg BIW or 50 mg QW for 12 weeks (double-blind phase) and ETN 50 mg QW for 12 additional weeks (open label). In this analysis, only patients from Czech Republic, Hungary, Poland and Serbia were included. The primary efficacy variable was the proportion of subjects achieving a physician global assessment (PGA) of psoriasis status: "clear" or "almost clear" at week 12. Results: In the 307 patients, 54% BIW/QW compared with 40% (QW/QW) ( p = .02), achieved "clear"/"almost clear" for PGA of psoriasis at week 12 increasing, to 68% and 60%, respectively ( p = .134) by week 24. Mean improvement from baseline in PASI were 59% versus 49% ( p = .005) at week 6 and 87% versus 81% ( p < .05) at week 24, for the BIW/QW and QW/QW groups, respectively. ETN was well tolerated in both groups over 24 weeks. Conclusions: Both dose regimens of ETN provided significant improvements in efficacy in PsA treatment and were well tolerated.